Three different calculations to compute a swimmer's instantaneous active drag profile and variations in the parameter values that arise as a consequence - Mason, B. R.; Sacilotto, G. B.; Hazrati, P.; Franco, R. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The Australian Institute of Sport has developed a free swim analysis system called the Assisted Towing Method (ATM), designed to estimate a swimmer's instantaneous whole body active drag force profile at the swimmer's maximum swim velocity. From the swimmer's active drag profile and acceleration profile, the propulsive force profile may also be computed (Mason et al. 2012). The resultant or net force profile for the swimmer may then be computed as the sum of both the predominantly negative active drag and the predominantly positive propulsive force profile. These three profiles may then be used to assist in the biomechanical assessment of the swimmer's free swimming technique. Two major research systems have previously investigated the active drag experience by a swimmer. The first of these was the Measurement of Active Drag (MAD) system in which the swimmer pulled on levers under the water to propel himself. The levers were mechanically linked to a force transducer (Toussaint et al. 2004). This provided a mean propulsive force value which automatically equated to a mean active drag force value. The second system developed was the velocity perturbation method (VPM) in which the swimmer swam twice at maximum speed, once towing and being resisted by a hydrodynamic body and then again without the hydrodynamic body attached (Kolmogorov et al. 1992). Through a computation using the two mean swim velocity values and the mean resistance force value of the hydrodynamic body, a mean active drag force value at the swimmer's maximum swim velocity was able to be computed. The ATM method involves towing the swimmer at a five to eight percent greater speed than the swimmer's maximum swimming velocity, utilising a tow which allows a swimmer's natural intra stroke velocity fluctuations to occur. The swimmer must apply equal mean maximum power and use a similar swimming technique in both the assisted swim with the tow and the unassisted swim, as well as maintain a mean constant speed throughout both conditions. The varying drag force as measured with the force platform and the two varying velocity profiles obtained from the dynamometer are used in the computation of active drag. The drag force and velocity parameters are sampled over four freestyle strokes, commencing with a right hand entry after the swimmer has attained the set mean tow velocity. A cubic function obtained by using the maximum swim velocity and the tow velocity is used to compute the swimmer's active drag parameter by multiplying the drag force profile by this cubic function (Mason et al. 2011). In this research project three different calculations were made. In the first calculation, just the two mean velocities (maximum swim velocity and tow velocity) are used in the cubic function. In the second calculation the two instantaneous variable velocities are used. In the third calculation an additional factor incorporating the acceleration profile is applied to the second calculation.